Medicolegal Importance of Sex Determination with the Help of Lip Prints: Cheiloscopy - Imran Jawaad, Muhammad Mushtaq, Farazen Sadia Mushtaq, Zoya Imran, Samreen Rizwan, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Identification whether of living person or of dead bodies have always been an uphill task for forensic experts. Traditional ways of identification are used commonly due to limited resources and lack of trained personals in the relevant field. Identification becomes very important when victim or assailant is unknown. To establish identification, methods commonly used are finger prints, foot prints, DNA technology. Lip prints a relatively neglected field of identification can be used to establish identification and sex determination producing almost same results as other methods of identification. Objectives: To determine whether lip prints can be used from their configuration to determine the gender identification. Material and Method: 75 medical college students with equal gender distribution, 35 male and 35 females were included in the study. Students were aged between 18 to 25 years. Inclusion criteria: Students with no lip abnormality were included in the study. Exclusion criteria: Students with any abnormality of lips or who have some lip surgery were excluded from the study. Results: The uniqueness of the lips was established by the facts that no two lips matched with each other. Females revealed type I, I’ most abundant, whereas type IV was abundantly observed among males. From the current study, with inexperienced observers it was revealed that from sample of 20 lip patterns from each gender, 18 females and 17 males were easily identified. Conclusion: Identification of a person whether living or dead is a challenging task for forensic experts around the globe. Lip prints are among the cheapest and easily available methods of identification producing almost same results as finger prints. It is a rather neglected area which needs to be focused more as it is cheap and can be equally effective in producing almost same results as other related methods used for identification and sex determination in particular unknown cases. Keywords: Sex determination, Lip prints, Medicolegal importance